Microsatellite loci for population and parentage analysis in the Amazon River dolphin (Inia geoffrensis de Blainville, 1817) - Gravena, Waleska; Hrbek, Tomas; Silva, Vera Maria Ferreira da; Astolfi-Filho, Spártaco A.T.; Farias, Izeni P. (Molecular Ecology Resources, 2009)
We developed specific primers for microsatellite DNA regions for the Amazon River dolphin or boto Inia geoffrensis, for use in population and conservation genetic studies. We also tested their transferability for two other species, Pontoporia blainvillei (sister taxon of I. geoffrensis) and Sotalia guianensis. A total of 12 microsatellite loci were polymorphic for the boto. An additional 25 microsatellite loci previously isolated from other cetacean species were also tested in the boto. The 26 polymorphic microsatellite loci indicate they will be excellent markers for studies of population structure and kinship relations of the boto. © 2009 Blackwell Publishing Ltd.
Keywords: Cetacea; Inia Geoffrensis; Pontoporia Blainvillei; Sotalia Guianensis